The Expediency of Research in the Field of Family Business (Путеводитель предпринимателя)
The present article deals with the key reasons for the absence of research in the field of family business in Russia, which could be explained mainly by the lack of interest on the part of business community. The principle objective is to study family business from the point ofview of retaining the company after its transfer to the next generation of owners. The author substantiates the expediency of wide-scale research of family business in Russia in order to restore the family business tradition and to minimize errors that family businesses in Western countries faced.